INTEGRASI ILMU FALAK DAN TRADISI BUGIS DALAM LONTARA’ OMPO’NA ULENG NGE TERHADAP PEMAHAMAN MASYARAKAT DI KECAMATAN LANRISANG KABUPATEN PINRANG - Arfiani, Andi Fitri; Fatmawati, Fatmawati (Universitas Islam Negeri Alauddin Makassar, 2026)
ABSTRACT This study examines the integration of astronomy and Bugis traditions in the Lontara' Ompo' Na Uleng Nge and its influence on community understanding in Lanrisang District, Pinrang Regency. The research method used was field research with a qualitative approach, encompassing sharia, astronomy, and ethnography. Data were obtained through observation, interviews, and documentation from community leaders, village imams, and traditional figures. Data processing and analysis involved three stages: data reduction, data presentation, and drawing conclusions or data verification. The results indicate that the Lanrisang community uses a traditional calendar system based on the Lontara' Ompo' Na Uleng Nge, which refers to the orbit of the moon and stars as a guide for traditional timing. This system contains spiritual, social, and ecological values, reflecting the interconnectedness of local wisdom and traditional astronomy. This study emphasizes the importance of preserving the local calendar system as a cultural heritage that integrates tradition, astronomy, and religious values, and encourages local government support for the development and documentation of this knowledge to ensure its relevance in the modern era.